1998
DOI: 10.1111/j.1469-7793.1998.235by.x
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline secretion by frog gastric glands measured with pH microelectrodes in the gland lumen

Abstract: In the present work we have measured the pH of the secreted fluid within the gland lumen of isolated but intact gastric mucosa of Ranaesculenta. Tissues were mounted in a double chamber allowing continuous perfusion of the mucosal and serosal compartment, and the measurements were made with double‐barrelled pH glass microelectrodes inserted into the glands from the serosal surface under microscopic inspection. During inhibition of H+ secretion by cimetidine (100 μm) the luminal gland pH (pHgl) averaged 7.60 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…This idea derives from our observations both in this (Fig. 9A, gray plot) and in previous studies (24) that in the 6 -10 min before pH gl starts to decline, a transient and small but significant alkalinization of the gland lumen was measured in 50% of the gland lumina. Second, as a result of K ϩ and HCO 3 Ϫ efflux, an osmotic gradient sufficient to drive water into the gland lumen is created.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This idea derives from our observations both in this (Fig. 9A, gray plot) and in previous studies (24) that in the 6 -10 min before pH gl starts to decline, a transient and small but significant alkalinization of the gland lumen was measured in 50% of the gland lumina. Second, as a result of K ϩ and HCO 3 Ϫ efflux, an osmotic gradient sufficient to drive water into the gland lumen is created.…”
Section: Discussionmentioning
confidence: 74%
“…Fast fluid exchange in the chamber was achieved within seconds from a shock-free, electronically controlled eight-way manifold. TEA ϩ -sensitive Microelectrodes-Double-barreled TEA ϩ -sensitive microelectrodes were constructed as described previously for pH-sensitive microelectrodes (24,32). Briefly, two pieces of filament-containing aluminum silicate glass tubing of different diameter (1.5-mm outer diameter and 1.0-mm inner diameter and 1.1-mm outer diameter and 0.75-mm inner diameter) (Hilgenberg, Malsfeld, Germany) were fixed in parallel and melted together by first twisting and then untwisting them at melting point before they were pulled in a PE2 vertical puller (Narishige, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…This action would act in concert with the increase of paracellular diffusion of other low molecular weight molecules (Papini et al ., 1998) to provide a selective advantage to toxin‐producing strains in the nutrient‐poor environment of the gastric mucous layer. In addition, the predicted increased secretion of carboxylates and, more importantly, of HCO 3 − is expected to counteract, together with bacterial urease, the acidification of the mucous layer due to proton diffusion from the stomach lumen, or to alter acid secretion by oxyntic cells (Debellis et al ., 1998). A leak of the alkaline anion HCO 3 − through the apical membrane of gastric superficial epithelia would be a relevant physiological change mediated by VacA, since it has been shown that this membrane is non‐permeable to this ion under physiological conditions (Caroppo et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we applied Ca 2+ ‐selective microelectrodes in order to quantitatively assess dynamic changes in extracellular [Ca 2+ ] in the extracellular fluids of the gastric gland lumen and the basolateral interstitial spaces of the intact amphibian gastric mucosa, taking advantage of an electrophysiological technique originally developed in our laboratory to measure pH in restricted extracellular compartments (Debellis et al ., 1998). Substantial decreases and increases in extracellular [Ca 2+ ] were recorded at the basolateral and apical microdomains, respectively, of the epithelium in response to a Ca 2+ ‐mobilizing agonist (carbachol).…”
Section: Introductionmentioning
confidence: 99%